O branco é o Drácula? Branquitude, discursos e arenas educativas - Vieira, Marciene da Silva (2023)
This research is the encounter, becoming, becoming of the researcher with the theme whiteness. The investigation proceeds from the problematics: How does a discursive matrix about whiteness, materialized in scientific works, work and order the capillarity of the theme-notion? What are the constitutive elements of whiteness and how do they slide/echo in the discursive order? What senses of whiteness are controlled? Which ones are banned? This design sought to understand the possibilities of analyzing whiteness as a political discursive matrix, in which there is consensus and dissent, invisible visibilities and visible invisibilities. Some specific objectives were broken down: to discuss different mechanisms of racism and colonialism; investigate how meanings have been produced for whiteness in literature and scientific research (theses and dissertations); to build constitutive elements of a discursive matrix of whiteness based on scientific research; make the question “Is the white Dracula?” as a creative power, in the meaning of re/thinking the way(s) in which whiteness slide/echo in the discursive provenance. In this sense, the methodological ritual was built with inspiration in the work of Michel Foucault, in the attempt to find the conditions that would make it possible to think about the origin of these discourses and the exclusion procedures that act on them (interdiction, separation, rejection and opposition of the true and of the fake). The theoretical framework for understanding the machinery of coloniality, the constitution of racial hierarchies and the emergence of the theme-notion of whiteness were the works of Cida Bento (2002; 2022), Lia Vainer Shucman (2012; 2014; 2018; 2023), Sueli Carneiro (2023), Denise Ferreira da Silva (2022), Grada Kilomba (2021), bell hooks (1995; 2017; 2019), Lourenço Cardoso (2008; 2014; 2017; 2022). The materiality of the research consisted of twenty-four academic productions, including theses and dissertations, produced in the area of Education, between 2018 and 2023. In these texts, whiteness was defined as a norm, white racial identity, ideology, as a synonym of whiteness (phenotype ), place of speech, device and as discursive formation. The constitutive elements of whiteness found by the authors were: privileges/meritocracy; white supremacy/superiority, invisibility/neutrality. With these findings, we are faced with the following question: is whiteness something or is it something that is put into operation? The discursive matrix of whiteness mobilizes and enhances these meanings and constitutive elements. Thus, when we ask “Is white Dracula?” we conclude that Dracula can be many things, not being [only] the white-skinned guy who does not see himself racialized, but it is in the Dracula-mirror relationship that whiteness is made, that it operates. The discursive game is paradoxical, while whiteness invents and arranges disputes and alliances to continue “not reflecting itself”, it reinforces and gives visibility to capillarities of discursive practices, real wills and power relations in an educational arena of the social and cultural. Being plural and in constant dispersion, whiteness does not “is”, it works in authorization and interdiction, in silencing and in the discursive pact.